The effectiveness of tourism development in social cultural approach in Sabah - Mohamad Pirdaus Yusoh; Ang, Kean Hua; Normah Abdul Latip; Zulayti Zakaria; Dg Junaidah Awang Jambol; Mohammad Al Amir As Khairullah; Ridzuan Abd Gafor (Malaysia Institute of Planners, 2023)
The generation of the national economy also lists the tourism industry as one of the sectors that need to be taken into consideration, primarily through social-cultural that has its characteristics to attract foreign tourists to visit the state of Sabah. This research study was conducted to investigate and evaluate the effectiveness of tourism development on social-cultural in Sabah. This research uses a quantitative approach, where questionnaires are the main instrument in collecting data in Sabah. The questionnaire format’s structure is divided into two, namely, part A (focused on the demographic profile) and part B (concentrate on the cultural-social approach in tourism development in Sabah). The study sample was a total of 74 respondents, and the questionnaire was distributed randomly in the tourist focus area of Kota Kinabalu. The analysis used is descriptive and correlational. The findings of the study indicate that the majority of cultural variables and social variables are centered on a positive curve (or towards the right), where most respondents think that local government programs and activities help a lot in understanding the cultural-social importance of the tourism sector. In addition, the uniqueness and privilege of cultural-social tourism, such as through clothing, food, wedding events, dance, etc., can play a significant role in the development of tourism. In conclusion, cultural social tourism should be the main theme not only for the generation of the national economy but also crucial in the preservation and conservation of the continuity of Sabah's local cultural-social tourism characteristics, which should be preserved in their originality forever rather than being outdated by the era of modernization.